A Reliability Generalization Meta-Analysis of Quality of Work Life (QWL) Scale - Ozyavas, Sinan (Routledge Journals, Taylor & Francis Ltd, 2025)
The objective of this study was to estimate the overall reliability values of the QWL scale, to investigate the variability of QWL scale score reliability across studies, and to estimate induction rates. A comprehensive literature review was conducted using Web of Science, Scopus, Science Direct, ProQuest, and Google Scholar. The reliability generalization meta-analysis was performed using 55 alpha coefficient estimates from 53 studies that met the selection criteria. Transformed coefficient values by Bonett's method were utilized. The mean transformed coefficient alpha value was estimated at .877 (95% CI = .862, .890). This value is statistically significant under the random effects model (p < .001). To further investigate the variability of reliability estimates in ANOVA and meta-regression analyses, moderators were coded. The results showed that mixed participant samples had a statistically significant effect on reliability estimates. Suggestions were made for researchers and counselors using the QWL scale.
Keywords: RG meta-analysis; alpha coefficient; quality of work life; reliability generalization; meta-analysis